Flying Blind? : Constructing Evidence-based Poverty Reduction Policies in PRSP Adopting Countries /: Constructing Evidence-based Poverty Reduction Policies in PRSP Adopting Countries. (March 2009) - (Doctoral student in economics), Marshall, Richard; Walters, Bernard; Nixson, F. I
No abstract available